Second generation leptoquark earch in pp̄ collisions at √s = 1.8 TeV - Abachi, S; Abbott, B; Abolins, M; Acharya, B; Adam, I; Adams, D; Adams, M; Ahn, S; Aihara, H; Alitti, J; Álvarez, G; Alves, G; et al. (1995)
We report on a search for second generation scalar leptoquarks with the D0 detector at the Fermilab Tevatron pp̄ collider at √s = 1.8 TeV. This search is based on 12.7 pb-1 of data. Second generation leptoquarks are assumed to be produced in pairs and to decay into a neutrino and quark with branching ratio β or into a neutrino and quark with branching ratio 1 - β. We obtain cross section times branching ratio limits as a function of leptoquark mass and set lower limits on the leptoquark mass at the 95% confidence level.